What future for Kirkuk? Evidence from a deliberative intervention. Issue 7 (3rd October 2019) - O'Flynn, Ian; Sood, Gaurav; Mistaffa, Jalal; Saeed, Nawhi
ABSTRACT: The "youth bulge" in developing countries means that we need to pay close attention to how young people want to be governed. That need is particularly great in developing countries that are also deeply divided. But in divided societies, conventional opinion polls often do not suffice, yielding shallow opinions hostage to elite machinations and mutual mistrust. To shed light on what young people would want if they had a chance to learn and deliberate about the issues, we follow a survey with an intensive deliberative field experiment in one such society – Kirkuk. Contrary to widespread concerns about the predominance of ethnic interests, young educated Kirkukis support the view that different ethnic groups should have an equal say. There is also broad support for an institutional arrangement – Kirkuk's becoming an autonomous region – that may provide space for instituting "equal say". And deliberating with balanced information broadens support for that arrangement.